COMMUNICATION STRATEGY AS FACEBOOK SOCIAL NETWORK MARKETING E-COMMERCE MEDIA COMMUNITY SURABAYA (Descriptive Study-Qualitative Sports Equipment Products) - Juwito Juwito; Saifuddin Zuhri (Jurnal MEBIS (Manajemen dan Bisnis), 2020)
In 2014 Indonesia has some young leaders who are well-known as a businessman in the field of e-commerce on the scope of South-East Asia. Therefore, this study aims to Determine the marketing communication strategy of e-commerce in using social networking sites namely Facebook, but anyway the government did not have any collection of data about e- commerce activities. Data source in this study is as much as three informants from community members who use Facebook doing e-commerce for selling sports equipment. The data analysis technique used is the depth interview. The Results Showed that E-commerce in Facebook classified to direct the marketing communications mix Showed Because this study informants that use only the medium of Facebook to promote Reviews their e-commerce activity. E- commerce activities are performed as informants Also inspired by other friends who has already doing e-commerce there. The success of the predecessor as well as has motivated them to Participate in implementing e-commerce activities.